Cooperative Signaling with Soft Information Combining. (6th December 2009) - Lin, Rui; Martin, Philippa A.; Taylor, Desmond P.
Abstract : We propose a Decode-and-Forward (DF) scheme using distributed Turbo code (DTC) for a three-node (source, relay, and destination) wireless cooperative communication system. The relay decodes, then interleaves, and reencodes the decoded data. It then forwards the reencoded packet and its instantaneous receive SNR to the destination. The performances using both ideal and quantized SNR are studied. The destination uses a modified metric within a Turbo decoding algorithm to scale the soft information calculated for the relay code. The proposed scheme is simple to implement and performs well.